2017
DOI: 10.1016/j.joco.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adjuvant omega-3 fatty acid supplementation on dry eye syndrome following cataract surgery: A randomized clinical trial

Abstract: PurposeTo investigate the effect of omega-3 polyunsaturated fatty acid supplement on qualitative and quantitative subjective (ocular surface disease index [OSDI]) and objective (Schirmer's test, tear break up time [TBUT], and tear osmolarity) dry eye indices after cataract surgery.MethodsIn this randomized clinical study, 61 eyes of 48 patients complaining of new onset dry eye symptoms after phacoemulsification were enrolled. Subjects were randomly allocated into two groups using urn randomization. Controls re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…There is evidence to suggest that omega-3 fatty acid supplementation may improve the signs and symptoms of DED, with a recent meta-analysis of randomized controlled trials by Giannaccare et al indicating that omega-3 supplementation may be effective in the management of DED. 133 In the context of DED post-cataract surgery, a RCT by Mohammadpour et al 134 indicated that compared to controls receiving conventional postoperative treatment, patients receiving omega-3 supplements (1000 mg 8 hourly for 1 month) after cataract surgery had better OSDI scores and higher TBUTs, suggesting that this may be a useful adjunctive therapy for those patients with newly diagnosed DED after cataract surgery as well as for those with pre-existing DED undergoing surgery.…”
Section: Other Treatment Interventionsmentioning
confidence: 99%
“…There is evidence to suggest that omega-3 fatty acid supplementation may improve the signs and symptoms of DED, with a recent meta-analysis of randomized controlled trials by Giannaccare et al indicating that omega-3 supplementation may be effective in the management of DED. 133 In the context of DED post-cataract surgery, a RCT by Mohammadpour et al 134 indicated that compared to controls receiving conventional postoperative treatment, patients receiving omega-3 supplements (1000 mg 8 hourly for 1 month) after cataract surgery had better OSDI scores and higher TBUTs, suggesting that this may be a useful adjunctive therapy for those patients with newly diagnosed DED after cataract surgery as well as for those with pre-existing DED undergoing surgery.…”
Section: Other Treatment Interventionsmentioning
confidence: 99%
“…The intake of ω3 PUFAs also accelerated epithelial healing, improved TBUT, and facilitated visual recovery after photorefractive keratectomy [58]. Oral supplementation of ω3 PUFAs was associated with additional improvements in tear stability and osmolarity as well as symptoms associated with DED after phacoemulsification surgery [59]. Park et al [60] demonstrated that oral supplementation of EPA and DHA for 2 months might improve ocular surface symptoms and inflammation, rather than tear secretion, in DED after cataract surgery.…”
Section: Oral Supplementation Of ω3 Pufas For Dedmentioning
confidence: 99%
“…Based on these mechanisms, methods to reduce the extent of corneal incision, operation time, exposure to causal factors listed above, and manipulation of the cornea during surgery have been proposed [12]. Reports have indicated that common treatments of dry eye syndrome such as ocular surface anti-inflammatory treatment [13], artificial tears, and omega-3 fatty acid ingestion [14] improve symptoms to a certain extent [15], but a confirmed treatment method that prevents and improves patient discomfort is not yet known.…”
mentioning
confidence: 99%